Nursing Management Information System for Monitoring Hand Hygiene Compliance of Health Care Workers - Aris Teguh Hidayat; Weni Apriyani; Desy Anggraini (Jurnal Kesehatan, 2025)
Introduction: Healthcare Associated Infections (HAIs) are one of the health problems in developed and developing countries, the incidence of nosocomial infections occurs almost all over the world and greatly affects developing and poor countries. One way or effort that can be done to prevent nosocomial infections is by hand decontamination where disease transmission through hands can be minimized by maintaining hand hygiene by means of hand hygiene. Results: The advancement of information system technology is growing rapidly along with the needs of humans as its users. The benefits of information system technology can also be enjoyed and applied in the health sector. Management information systems can also be utilized in health promotion efforts, namely in efforts to monitor hand hygiene compliance. Efforts to monitor hand hygiene compliance consist of hardware as a recording tool, and software as a processor to present the required data. Efforts to apply observation technology using the latest tools integrated with the management information system are expected to be a solution to the shortcomings of direct observation carried out by officers including human error susceptibility, data presented, and solutions to the time taken from the documentation collection process. Conclusion: The author uses literature studies as a writing method. This article presents recommendations for the health care sector to use integrated management information system technology as an effort to improve the quality of health care, especially in the field of nursing based on evidence-based practice.